Magnolia x soulangiana 'Pristine' 'Pristine' Saucer Magnolia: FPS-373/FP373, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the ‘Pristine’ saucer magnolia (Magnolia x soulangiana ‘Pristine’), detailing its characteristics, planting requirements, and care guidelines. The tree is noted for its upright, round habit, moderate growth rate, and showy white flowers that bloom in late winter to early spring. It thrives in USDA hardiness zones 5 through 9A and can be planted year-round in zones 7 to 9. The ‘Pristine’ saucer magnolia is suitable for various uses, including near patios, in containers, or as an espalier. It is generally pest-free but may be affected by scales and leaf spots. The document emphasizes the importance of early training to develop the desired form and highlights the tree’s ornamental features, such as its winter interest and attractive bark. Original publication date October 1999.